Synergistic effects of Monel 400 filler wire in gas metal arc welding of CoCrFeMnNi high entropy alloy - Shen, Jiajia (2024)
Funding Information: JS and JPO acknowledge Fundação para a Ciência e a Tecnologia (FCT - MCTES) for its financial support via the project UID/00667/2020 (UNIDEMI). JPO acknowledges the funding of CENIMAT/i3N by national funds through the FCT-Fundação para a Ciência e a Tecnologia, I.P., within the scope of Multiannual Financing of R&D Units, reference UIDB/50025/2020-2023. JS acknowledges the China Scholarship Council for funding the Ph.D. grant (CSC NO. 201808320394). This work was supported by the National Research Foundation of Korea (NRF) with a grant funded by the Korea government (MSIP) (NRF-2021R1A2C3006662). The authors acknowledge DESY (Hamburg, Germany), a member of the Helmholtz Association HGF, for the provision of experimental facilities. Beamtime was allocated for proposal I-20210899 EC. The research leading to this result has been supported by the project CALIPSOplus under the Grant Agreement 730872 from the EU Framework Programme for Research and Innovation HORIZON 2020. Funding Information: JS and JPO acknowledge Funda\u00E7\u00E3o para a Ci\u00EAncia e a Tecnologia (FCT - MCTES) for its financial support via the project UID/00667/2020 ( UNIDEMI ). JPO acknowledges the funding of CENIMAT/ i3N by national funds through the FCT- Funda\u00E7\u00E3o para a Ci\u00EAncia e a Tecnologia , I.P., within the scope of Multiannual Financing of R&D Units, reference UIDB/50025/2020-2023. JS acknowledges the China Scholarship Council for funding the Ph.D. grant ( CSC NO . 201808320394 ). This work was supported by the National Research Foundation of Korea (NRF) with a grant funded by the Korea government (MSIP) (NRF-2021R1A2C3006662). The authors acknowledge DESY (Hamburg, Germany), a member of the Helmholtz Association HGF, for the provision of experimental facilities. Beamtime was allocated for proposal I-20210899 EC . The research leading to this result has been supported by the project CALIPSOplus under the Grant Agreement 730872 from the EU Framework Programme for Research and Innovation HORIZON 2020 . Publisher Copyright: © 2024 The Authors